Analysis Nutritional of Tabantal Plant (Similax sp.)Feed Addition to Poultry - Lumban Gaol, Susan E. (Journal of Tropical Animal Science and Technology, 2025)
Local plant feed ingredient tabantal Similax sp. Kalimantan's typical forest plants are one of the resources that provide benefits to humans both economically. The aim of this research is to determine the nutritional content of the Similax sp plant which can be utilized by the people of Kalimantan. This research is a qualitative research by describing the results of the analysis of two research stages, namely the manufacture of tabantal flour which was carried out at the Animal Husbandry Laboratory, Faculty of Agriculture, Antakusuma University, Pangkalan Bun. Meanwhile, proximate testing for water, ash, fat, protein, crude fiber and Ca content testing were carried out at the Animal Nutrition Laboratory, Faculty of Animal Husbandry, Bogor Agricultural Institute. The results of the proximate analysis of tabantal plants contained water content of 10.54%, ash content of 6.05%, fat 3.82%, protein 21.28%, crude fiber 17.82% and Ca 0.53%. From the results of this analysis, tabantal plants can be used as poultry feed.